Bribery and Corruption Casebook - Wells, Joseph T.; Hymes, Laura; Boehmer, Paul; Craden, Abby (Tantor Media, Inc., 2020)
This one-of-a-kind collection consists of actual cases written by fraud examiners out in the field. These cases were hand selected from hundreds of submissions and together form a comprehensive picture of financial statement fraud. The cases each are entertaining stories in their own right, as well as educational, and readers will enjoy reading them as they grow to understand more about how corruption and bribery occur and their impact on organizations.